Preparation And Characterization Of Supported Gold Nanoparticles And Their Catalytic Studies In The Reduction Of P-Nitrophenol - Yazid, Hanani (2010)
Gold (Au) nanoparticles supported on titania (TiO2), alumina (Al2O3) and zinc oxide (ZnO) were prepared by the deposition-precipitation (DP) method using gold (III) chloride trihydrate, HAuCl4.3H2O as the precursor. The effect of pH on Au loadings, particle size and particle size distribution in the preparation of the gold nanoparticles were studied at pH below and above the isoelectric points (IEP) of the metal oxide supports. The effects of adjusting pH before and after the addition of the support into the gold precursor solution were also investigated. Structural and elemental characterizations of the supported gold nanoparticles were carried out using X-ray diffraction (XRD), transmission electron microscopy (TEM), scanning electron microscopy (SEM), energy-dispersive X-rays (EDX), atomic absorption spectrometry (AAS), ultraviolet-visible spectroscopy (UV-Vis) and Brunauer, Emmett and Teller (BET) adsorption method. The results revealed the dependency of Au particles size on the gold precursor species present at the pH of the preparation. The Au particle size obtained range between 4 - 8 nm. The Au/ZnO system produced the smallest Au particles size (4.32 ± 1.26 nm). The effect of pH adjustment furthermore emphasized the crucial of pHt (pH after the addition of support to the gold precursor solution) in determining the types of gold complexes deposited on the support. The final pH (pHf) showed a more pronounced effect in terms of the total Au loadings in the sample.